A prospective study of pulmonary outcomes and chest computed tomography in the first year after COVID-19. Issue 2 (13th March 2023) - Lerum, Tøri Vigeland; Meltzer, Carin; Rodriguez, Jezabel Riverio; Aaløkken, Trond Mogens; Brønstad, Eivind; Aarli, Bernt B.; Aarberg-Lund, Kristine Marie; Durheim, Michael T.; Ashraf, Haseem; Einvik, Gunnar; Skjønsberg, Ole Henning; Stavem, Knut
COVID-19 primarily affects the respiratory system. We aimed to evaluate how pulmonary outcomes develop after COVID-19 by assessing participants from the first pandemic wave prospectively 3 and 12 months following hospital discharge. Pulmonary outcomes included self-reported dyspnoea assessed with the modified Medical Research Council dyspnoea scale, 6-min walk distance (6MWD), spirometry, diffusing capacity of the lung for carbon monoxide ( D LCO ), body plethysmography and chest computed tomography (CT). Chest CT was repeated at 12 months in participants with pathological findings at 3 months. The World Health Organization (WHO) ordinal scale for clinical improvement defined disease severity in the acute phase. Of 262 included COVID-19 patients, 245 (94%) and 222 (90%) participants attended the 3- and 12-month follow-up, respectively. Self-reported dyspnoea and 6MWD remained unchanged between the two time points, while D LCO and total lung capacity improved (0.28 mmol·min −1 ·kPa −1, 95% CI 0.12–0.44, and 0.13 L, 95% CI 0.02–0.24, respectively). The prevalence of fibrotic-like findings on chest CT at 3 and 12 months in those with follow-up chest CT was unaltered. Those with more severe disease had worse dyspnoea, D LCO and total lung capacity values than those with mild disease. There was an overall positive development of pulmonary outcomes from 3 to 12 months after hospital discharge. The discrepancy between the unaltered prevalence of self-reported dyspnoea and the improvement in pulmonary function underscores the complexity of dyspnoea as a prominent factor of long-COVID. The lack of increase in fibrotic-like findings from 3 to 12 months suggests that SARS-CoV-2 does not induce a progressive fibrotic process in the lungs. Even though an overall positive development of lung function is observed between 3 and 12 months after hospitalisation for COVID-19, the prevalence of dyspnoea and fibrotic CT findings remains unaltered, independent of disease severity in the acute phase https://bit.ly/3gArGNh